Developmental Defects of Enamel and in Primary Teeth - Dr. Nauman Shirazi; DR KASHIF ADNAN; Zarafshan gul; Syeda Najia Abbas; PROFESSOR DR ASRAR AHMED; Dr Nabeel Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Developmental defects of enamel (DDE) in primary teeth are prevalent worldwide and can predispose children to early childhood caries (ECC). Objective: To assess the prevalence of DDE in primary dentition and examine associated risk factors, including birth weight and early life events. Methods: A descriptive cross-sectional study was conducted on 192 children aged 3 to 5 years using non-probability convenience sampling technique. Clinical examinations were performed by trained dental professionals using standardized criteria for diagnosing developmental defects of enamel (DDE) in primary teeth, based on the presence of hypoplasia, demarcated opacities, and diffuse opacities. Data on potential risk factors such as parental education, infection history, medication during lactation, formula feeding, and birth complications were collected. Statistical analysis involved Fisher exact tests with a significance level set at p<0.05. Results: Among the 192 participants, the frequency of enamel defects was 14.6% (n=27). Mild defects were observed in 5.21% (n=10), moderate defects in 3.13% (n=6), severe defects in 3.65% (n=7), and atypical restorations in 1.56% (n=3). Significant associations were found between enamel defect severity and paternal education (p=0.04) and medication use during lactation (p=0.039). No significant associations were found for maternal education, infection history, or birth complications (all p>0.05). Conclusion: The study found a 14.6% frequency of enamel defects among the study population. Paternal education and medication use during lactation were significant risk factors. These findings highlight the need for targeted preventive strategies and further research into the etiology of enamel defects.